ChemInform Abstract: Room Temperature Syntheses and Thermal Behaviors of Hydrogarnets Sr3M2(OH)12 (M: Al, Cr and Fe). Issue 26 (June 2015) - Chen, Yun‐Feng; Yang, Zhi; Li, Yong‐Ming; Guo, Jing; Fu, Wen‐Fu; Wang, Ying‐Xia; Liao, Fu‐Hui; Li, Jianye
Abstract Sr3M2(OH)12 (M = Al, Cr, Fe) are prepared by mechanical room temperature solid state reaction through quickly grinding mixtures of Al(NO3)3·9H2O or MCl3·6H2O (M: Cr, Fe), Sr(NO3)2, and 10 mol% excess solid NaOH.